Plasmodium vivax From Duffy-Negative and Duffy-Positive Individuals Share Similar Gene Pools in East Africa. (3rd February 2021) - Kepple, Daniel; Hubbard, Alfred; Ali, Musab M; Abargero, Beka R; Lopez, Karen; Pestana, Kareen; Janies, Daniel A; Yan, Guiyun; Hamid, Muzamil Mahdi; Yewhalaw, Delenasaw; Lo, Eugenia
Abstract: Plasmodium vivax malaria was thought to be rare in Africa, but an increasing number of P. vivax cases reported across Africa and in Duffy-negative individuals challenges this dogma. The genetic characteristics of P. vivax in Duffy-negative infections, the transmission of P. vivax in East Africa, and the impact of environments on transmission remain largely unknown. This study examined genetic and transmission features of P. vivax from 107 Duffy-negative and 305 Duffy-positive individuals in Ethiopia and Sudan. No clear genetic differentiation was found in P. vivax between the 2 Duffy groups, indicating between-host transmission. P. vivax from Ethiopia and Sudan showed similar genetic clusters, except samples from Khartoum, possibly due to distance and road density that inhibited parasite gene flow. This study is the first to show that P. vivax can transmit to and from Duffy-negative individuals and provides critical insights into the spread of P. vivax in sub-Saharan Africa. Abstract : Plasmodium vivax showed lower genetic diversity in Duffy-negative hosts but was not clearly differentiated from Duffy-positive hosts, suggesting between-host transmission. Parasites in Ethiopia and Sudan shared similar clusters, except for Khartoum, possibly due to distance and road density inhibiting gene flow.